Extraction of Temporal Features on Fibonacci Space for Audio Based Vehicle Classification - Sinha, Amandeep; Kumar, S. Hemanth; Prabhakar, Gudmalwar Ashishkumar; Rao, Ch V. Rama (Recent Trends in Image Processing and Pattern Recognition, 2022)
In this study we address automatic vehicle and engine identification based on audio information. This information be based on many factors, such as vehicle type, tires, speed, wear and tear of vehicles, as well as type of road. We have decided a feature set for discriminating pairs of classes. Feature set include Fibonacci feature space, entropy, skewness and kurtosis. The audio information collected are real time on-road recordings. There are four classes of vehicle sounds. The paper also shows problems related to vehicles classification. Classification on audio-based engine and vehicle type identification are proposed and conclusions are shown.